Practicing Matricentric Feminist Mothering - Green, Fiona Joy (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
The practice of feminist mothering is central to matricentric feminism because it is centred on the experiences of mothers. Mothering and feminism are equally defining dimensions in the lives of feminist mothers who recognize that although they are oppressed and disempowered both as women and as mothers by the patriarchal institution of motherhood, they, along with their children, can also be empowered through the conscious and active praxis of feminist parenting. By placing their needs and concerns as mothers at the centre of their feminist and political practice of parenting, feminist mothers engage in and offer others a praxis of matricentric feminism that incorporates maternal theory, activism, and feminist motherlines. This article reflects upon some of the lessons of matricentric feminism explored and detailed within my 2011 book Practicing Feminist Mothering. The book is based on two decades of research involving the lived experiences and knowledge of sixteen selfidentified feminist mothers and a number of their adult children. Although the experiences and findings may appear to be somewhat dated, the insights from this research, nevertheless, provide an understanding of the conscious and political action of feminist mothering towards changing society through their parenting. They also provide a powerful perspective on mothering as a central aspect of feminism that may act as a foundation for further alternative family structures.